Pengembangan, Validasi, dan Evaluasi Skala Minat Matematika untuk Remaja - Amanda La Hadi; Tandri Patih; Halistin Halistin (Jurnal Tadris Matematika, 2023)
This study aims to develop and validate a multidimensional instrument that will measure the interest in mathematics among Indonesian adolescents (aged 12-21 years). The developed instrument must meet psychometric standards in terms of content, construct, and concurrent validity. This instrument is called the “Skala Minat Matematika Remaja” (SMMR). The existence of SMMR is important because: (1) it is based on a validated structure and content of interest in the literature, (2) it accommodates the measurement of interest during adolescence, and (3) it specifically measures mathematics interest, which will be useful in the mathematics learning process. Three sample groups were taken from secondary school to university level to complete the SMMR instrument. A quantitative approach was used to test three types of validity. Construct validity was tested using exploratory and confirmatory factor analyses. Exploratory factor analysis (EFA) resulted in a 20-item SMMR with four dimensions (engagement, knowledge, emotions, and value) that explained 58% of the total variance. This indicates that the selected items can effectively explain the four dimensions of interest. Furthermore, confirmatory factor analysis (CFA) on the third sample group confirmed that SMMR is suitable for application among different groups of adolescents. SMMR scores showed a significant negative relationship between interest and age. This relationship indicates that SMMR has good concurrent validity.